Strengthening values in the Mentari Sehat Indonesia community in empowerment practices - Shubuha Pilar Naredia; S. Supriyanto (Universitas Muhammadiyah Malang, 2024)
In the present era, the concept of community empowerment, highlighted in the SDGs, has gained traction as a prevailing phenomenon on the global social landscape. Mentari Sehat Indonesia (MSI) implements a community empowerment practice based on noble values. To describe the noble values that exist in the MSI community in community empowerment practices and the stages of their internalization, the universal noble values category developed by Kluckhohn is used. This research is a single case study with data sourcing from informant, library study, written document and archive, and visual data collected through interview, observation and documentation. 12 people informant was selected purposively based on sex, leadership for regional subsidiary organization, and education level. Data was analyzed using an interactive model of analysis including data reduction, data display, and conclusion drawing as well as verification. Data validation was conducted using source triangulation technique. The study discovered several important values within the MSI Community, including views on life, work, ethics, nature, time, and relationships among people. The internalization of noble values was conducted by MSI community through value transformation, value transaction, and trans-internalization stages. These three stages seem to be a good strategy in forming work character for an organization or community.